INVESTIGATION OF THE EFEECT OF TBLT-BASED DIGITAL STORYBOOK ON STUDENTS’ WRITING COMPETENCY IN SMA N 1 BUSUNGBIU - Adi Darma, I Nyoman Satya Surya (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
This study aims to investigate the significant effect of TBLT-based digital storybook among eleventh-grade students’ writing competency in SMA N 1 Busungbiu, Buleleng in academic year 2023/2024. This study was uses quasi-experimental research with Post-test only control group design. 63 eleventh-grade students are participated as sample in this study in which assigned into two group; experimental group which consisted of 34 students and control group which consisted of 29 students. Three instruments were used for data collection, namely lesson plan, writing test and assessment rubric. The two classes were given different treatment; TBLT-based digital storybook was treated in Experimental group and Teacher’ usual method was treated in Control group, by the end of the treatment writing test was given to students. The data was analyzed by using Independent sample T-test. The finding showed that there was a significant effect of TBLT-based digital storybook on students’ writing competency in SMA N 1 Busungbiu. Students that learn using TBLT-based digital storybook showed better result compared to students that learn using teacher’ usual method. It was proven by the Sig. (2-tailed) value of independent T-test was 0.001. Thus, the significance value of the tests was less than 0.05. Additionally, the effect size value measured using Cohen’s d was 0.917. This large effect means that the integration of TBLT method with technology in form of TBLT-based digital storybook can provide a good influence to students' Writing competency if compared to the teacher’s usual method.